Superior thermal energy storage performance of NaCl-SWCNT composite phase change materials: A molecular dynamics approach. (15th May 2021) - Yu, Yinsheng; Zhao, Chenyang; Tao, Yubing; Chen, Xi; He, Ya-Ling
Highlights: The NaCl-SWCNT based CPCM were proposed and designed by materials design strategy. The thermal properties and microstructure of CPCM were investigated by MD simulation. The mechanism of desirable thermal performance enhancement was revealed from at nanoscale. Abstract: Molten salts are attractive candidate materials used for effective thermal energy transfer and storage, which can be applied in the concentrating solar power (CSP) system at high temperatures for efficient and continuous solar energy utilization. In this paper, in order to improve the thermal performance of NaCl based molten salt, the NaCl and single walled carbon nanotubes (NaCl-SWCNT) based composite phase change materials (CPCM) were proposed and designed by composition design strategy of materials. The thermal properties and the microstructure of CPCM systems were investigated by means of molecular dynamics (MD) simulation at nanoscale. The thermal properties including density, melting point, self-diffusion coefficient, thermal conductivity, melting enthalpy and specific heat capacity were predicted, the simulation results are in good agreement with the available experimental data, and the mechanism of desirable thermal performance enhancement was revealed from the microscopic point of view. It was found that the addition of SWCNT can effectively reduce the melting point of molten salts, so as to control the working temperature range of molten salts. With the increase of the SWCNT mass fraction, the thermal conductivity and specific heat capacity increase significantly with the maximum enhancement of 38.59% and 5.87%, respectively, but the melting enthalpy decreases by 36.37%. The above phenomena can be attributed to the variation of atomic energy from nanoscale. This study is expected to provide possible guidance on the design and application of molten salts based PCMs for thermal energy storage at high temperatures.